Pengaruh Influencer Characteristics terhadap Purchase Intention Gen Z melalui Brand Credibility dan Parasocial Relationship pada Beauty Product - Afina Aulya; Patrick Kevin Aritonang (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the effect of influencer characteristics on Generation Z’s purchase intention through the mediating roles of brand credibility and parasocial relationship in the context of skincare products on the TikTok platform. This research adopts a quantitative approach using a survey method, with data collected through questionnaires distributed to 220 Generation Z respondents in Jakarta who actively use TikTok and have been exposed to beauty influencer content. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results indicate that influencer characteristics have a positive and significant effect on purchase intention, brand credibility, and parasocial relationship. Furthermore, brand credibility and parasocial relationship are also found to have a positive and significant effect on purchase intention. In addition, brand credibility and parasocial relationship are proven to mediate the relationship between influencer characteristics and purchase intention. These findings provide important implications for skincare companies in designing influencer marketing strategies that emphasize brand credibility and emotional closeness with influencers to enhance Generation Z consumers’ purchase intention on the TikTok platform.